Effect of Platelet Encapsulated lloprost on Platelet Aggregation and Adhesion to Collagen and Injured Blood Vessels In Vitro - El-Gamal, B A B; Pfliegler, G; Crawford, N (Thrombosis and Haemostasis, 1992)
A novel approach to site-directed delivery of drugs in vivo using blood platelets as carrier vehicles is being investigated. In this context some initial studies are reported on the effect of platelet encapsulated anti-platelet drugs on platelet aggregation and adhesion to fibrillar collagen and injured arteries in vitro. The stable prostacyclin analogue lloprost has been encapsulated within human and pig platelets by high voltage electroporation (Hughes and Crawford 1989 and 1990). After resealing the platelets, the packaged drug has a negligible effect upon platelet adhesion to a surface of fibrillar collagen or to damaged aorta (stripped to the tunica media to simulate deep injury). The rate of platelet recruitment to the collagen shows no dose dependency with respect to intracellular lloprost concentrations. After high lloprost loading, as few as 2% drug loaded platelets in a mixture with control (sham encapsulated) platelets, inhibit agonist-induced platelet aggregation >50%. The prior deposition of a “lawn” of Iloprost-loaded platelets onto fibrillar collagen or damaged aorta has a substantial inhibitory effect (50–70%) upon the secondary recruitment of normal platelets compared with recruitment to a “lawn” of normal platelets. This inhibition of secondary recruitment occurs even in the presence of a platelet activator. If reduction of platelet recruitment to a vessel wall lesion results in a decrease in the local concentration of platelet granule-derived smooth muscle cell chemotactic and proliferative factors, this site-directed drug delivery may well have application for the prevention of restenosis following balloon angioplasty procedures.